2022
DOI: 10.3390/ani12192651
|View full text |Cite
|
Sign up to set email alerts
|

The Improvement of Porcine In Vitro Embryo Development through Regulating Autophagy by miRNA-143 Inhibition

Abstract: In vitro embryo research is an important stage for the advancement of many reproductive technologies in research and agriculture. For this reason, the improvement of in vitro embryo development is a strategic field worthy of investigation. Relatively little is known about miR-143 and its effects on autophagy associated with embryo development and in vitro embryo culture. In this study, we examined the effect of miR-143 (via mimics and inhibitors) on embryonic development threatened by microinjection after part… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 33 publications
0
2
0
Order By: Relevance
“…Interestingly, Li et al [ 89 ] reported that miR-451 downregulation in mouse and human oocytes affected pre-implantation embryogenesis by suppressing the Wnt signaling pathway, suggesting that miR-451 might serve as a novel biomarker of oocyte and embryo quality in ARTs. Another miRNA increased in BGE was miR-143 which has been found as involved in porcine embryo development [ 90 ]. By contrast, miR-184, with a role in supporting embryo development as mentioned above, showed lower abundance in good vs. poor embryos during co-culture with BOEC.…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, Li et al [ 89 ] reported that miR-451 downregulation in mouse and human oocytes affected pre-implantation embryogenesis by suppressing the Wnt signaling pathway, suggesting that miR-451 might serve as a novel biomarker of oocyte and embryo quality in ARTs. Another miRNA increased in BGE was miR-143 which has been found as involved in porcine embryo development [ 90 ]. By contrast, miR-184, with a role in supporting embryo development as mentioned above, showed lower abundance in good vs. poor embryos during co-culture with BOEC.…”
Section: Discussionmentioning
confidence: 99%
“…The proper timing of 6 h after the electrical activation of the oocytes has been explained previously (Ridlo et al, 2021(Ridlo et al, , 2022. At 6 h after activation, the zygotes were held with a holding pipette in a 4-μl drop of PZM-5.…”
Section: Microinjection 6 H After Electrical Activationmentioning
confidence: 99%